Phragmope discrepans, gen. & comb. nov. (Mesophyllaceae, Corallinales, Rhodophyta), the species known as 'Mesophyllum engelhartii' from South Africa. Issue 6 (8th August 2020) - Athanasiadis, Athanasios
ABSTRACT: Phragmope discrepans ( Lithothamnion discrepans ) is recognized as a new monotypic genus endemic to South Africa on account of several active modes of growth, including apical meristem replacement, production of cell bars in canals of multiporate conceptacles, and development of a second compact, imperforate roof over multiporate conceptacles. Meristem replacement involves up to three layers. Development of cell bars starts with production of projecting cells from basal cells of lining filaments, and these cells subsequently coalesce to form a barrier. Subepithallial divisions produce a second compact roof that is composed of 1–2 perithallial cells and a layer of epithallial cells. It is assumed that these novelties reflect evolutionary advancements to overcome competition and the environmental pressure that Phragmope experiences in the intertidal zone. The new genus is taxonomically distant to the Northern Hemisphere genus Mesophyllum, and relates closer to taxa from the Southern Hemisphere, including Melyvonnea that occurs in South Africa and species of Mesophyllum sensu lato from Chatham-New Zealand-Australia, which collectively display a reduced fusion cell and lack of a pedestal in carposporangial conceptacles. Previous molecular studies based on SSU rDNA sequences and including an isolate of ' M. engelhartii ' from South Africa support the same view. It is shown that the name 'Fam.Mesophylleae Dum.' Heeg [1891. Niederösterreiehische Lebermoose.- Verhandl. der k.k. zool.-botan. Gesellsch. in Wien 41:567–573] in Leverworts is invalid. Hence Mesophyllaceae Athanasiadis [2016. Phycologia Europaea Rhodophyta, Vols 1 & 2. Published by the author, Gothenburg. xlviii + 1504 pages] is available in the Corallinales (including Hapalidiales), while Mesophyllumaceae Schneider & Wynne (2019. Fourth addendum to the synoptic review of red algal genera. Botanica Marina. 62:355–367) becomes a later synonym.